CFD Simulation of Enhancement Techniques in Flat Plate Solar Water Collectors - Hassan, Jafar Mehdi; Abdul-Ghafour, Qussai J.; Mohammed, Mohammed F. (Al-Nahrain Journal for Engineering Sciences, 2017)
The present work is a numerical study of thermal performance of modified flat plate solar water collectors. Numerical simulations have been done by solving the governing equations (Continuity, Momentum and Energy) equations in the laminar regime , three dimensions by using the FLUENT software version (14.5). The effect of flow on temperature distribution of flat plate water collectors by inserting (twist strip with twist ratio (3), helical spring surrounding the solid shaft) inside riser pipes is numerically simulated and compared with solar collector without inserting device inside its riser pipes at flow rates of (100)?/h . The numerical simulation results show that the flat plate water, solar collectors with the inserted, twist strip and helical spring that’s surround the solid shaft were higher enhancement of heat transfer than without inserted devices. The useful energy in case of twist strip is (10%) higher than the case of flat plate solar collector without enhancement device. Also, the case of helical spring is increased (6.8 %) than the twist strip, and (16.2%) than collector without enhancement device for the same mass flow rate.